2014
DOI: 10.1080/07391102.2014.909743
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the anti-HIV Nikavir prodrug: comparisons with AZT and Thymidine, and establishment of structure–activity relationships/tendencies in other 6′-derivatives

Abstract: A comprehensive theoretical conformational analysis of the anti-HIV Nikavir prodrug was carried out; this prodrug has noticeable advantage over the approved drug AZT. The whole conformational parameters (χ, α, β, γ, δ, ϕ, P and νmax) were analysed as well as the NBO natural atomic charges. The calculations were carried out by means of DFT/B3LYP and ab initio MP2 methods with full relaxation of all geometrical parameters. The search located at least 67 stable structures, 4 of which were within a 1 kcal/mol elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 88 publications
2
24
1
Order By: Relevance
“…In general, DFT methods appear as the most suitable today because they offer a compromise between the important demands put on computer power and time, and the desired chemical accuracy. Furthermore, these methods have been used satisfactorily in many spectroscopic studies, in nucleosides, DNA base pairs, water cluster of nucleobases, biological molecules, and in drug designing, in particular the M062X method selected here …”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, DFT methods appear as the most suitable today because they offer a compromise between the important demands put on computer power and time, and the desired chemical accuracy. Furthermore, these methods have been used satisfactorily in many spectroscopic studies, in nucleosides, DNA base pairs, water cluster of nucleobases, biological molecules, and in drug designing, in particular the M062X method selected here …”
Section: Computational Methodologymentioning
confidence: 99%
“…Several parameters characterize the conformation of a nucleotide, namely the orientation of the purine/pyrimidine base unit regarding the furanose sugar unit (SU), the conformation of SU, and the orientation of the phosphate unit with reference to SU. Following the Saenger's notation, the atomic description of a nucleotide as well as the main endocyclic and exocyclic torsional angles appears as described in Scheme .…”
Section: Definition Of the Parameters In The Microhelixmentioning
confidence: 99%
“…Applied level of theory has successfully proved itself for the calculations of the similar systems [38]- [41]. A scaling factor that is equal to 0.9668 [42]- [45] has been applied in the present work for the correction of the harmonic frequencies of all conformers and TSs of their conformational transitions. We have confirmed the local minima and TSs, localized by Synchronous Transitguided Quasi-Newton method [46], on the potential energy landscape by the absence or presence, respectively, of the imaginary frequency in the vibrational spectra of the complexes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this task was undertaken in a similar way to that carried out in several NSs 19,92,93 and NDs, 44,94 but including in this case the M06-L and M05-2X methods, i.e. A full conformational study of this molecule has not been reported yet.…”
Section: Simulation Of the 1st Phosphorylation Stepmentioning
confidence: 99%